2019
DOI: 10.1108/jmhtep-07-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of depression literacy between pharmacy and non-pharmacy students of a Nigerian university

Abstract: Purpose The purpose of this paper is to assess and compare the knowledge and help-seeking behaviors toward depression among pharmacy students and non-pharmacy students. Design/methodology/approach The study was a cross-sectional descriptive survey and was carried out among undergraduate students of the oldest and largest university in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has long been reported that the extant pharmacy curriculum in Nigeria is ineffective to provide adequate training as per emerging mental and public health services for pharmacy graduates, as community pharmacists do highlight inadequate knowledge as one of the barriers to their provision of certain health services such as tobacco harm reduction and social health advice [ 7 , 8 ]. A study by Aluh et al [ 9 ] reported a greater level of depression literacy among pharmacy students in comparison with non-pharmacy students in one university, however, another study found an overall negative perception and attitude towards mental illnesses among pharmacy students as comparable to non-pharmacy students in another university suggesting deficient mental health literacy [ 10 ]. Furthermore, another study found a gross level of dissatisfaction among final year pharmacy students with the adequacy of their training to offer mental health services.…”
Section: Commentarymentioning
confidence: 99%
“…It has long been reported that the extant pharmacy curriculum in Nigeria is ineffective to provide adequate training as per emerging mental and public health services for pharmacy graduates, as community pharmacists do highlight inadequate knowledge as one of the barriers to their provision of certain health services such as tobacco harm reduction and social health advice [ 7 , 8 ]. A study by Aluh et al [ 9 ] reported a greater level of depression literacy among pharmacy students in comparison with non-pharmacy students in one university, however, another study found an overall negative perception and attitude towards mental illnesses among pharmacy students as comparable to non-pharmacy students in another university suggesting deficient mental health literacy [ 10 ]. Furthermore, another study found a gross level of dissatisfaction among final year pharmacy students with the adequacy of their training to offer mental health services.…”
Section: Commentarymentioning
confidence: 99%